„Sprache macht den Freigang der Gedanken möglich“. Zu den sprichwörtlichen Aphorismen von Franz Hodjak - Wolfgang Mieder (Linguistische Treffen in Wrocław)
The author Franz Hodjak, born on September 27, 1944 in Romania and living in Germany since October 19, 1992, has become known through his poems and novels. Between 2006 and 2023 he published four significant books of aphorisms with which he has made a name for himself as a writer of aphorisms. Of his about 3500 texts 265 or 7.5% are so-called proverbial aphorisms that despite their shortness contain proverbial language. Hodjak frequently starts with folk and Bible proverbs whose wisdom he puts into critical question by way of alterations and additions. Such anti-proverbs express his humorous, ironic or cynical view of modern life. That is also the case with numerous proverbial expressions whose metaphors add an impressive expressiveness to his thoughts. Somatisms, sometimes two in one text, are especially effective expressions to deal with social and human conditions. He employs formulaic linguistic structures and deals with such themes as truth, lie, love, religion, morality, politics, and much more. At all times he is concerned about human behavior in modern existence. Despite his cultural pessimism some of his aphorisms contain a glimmer of hope for a better world.